Effects of Antioxidant, Anti-Collagenase, Anti-Elastase, Anti-Tyrosinase of The Extract and Fraction From Turbinaria decurrens Bory. - Nurrochmad, Arief; Wirasti, Wirasti; Dirman, Arifin; Lukitaningsih, Endang; Rahmawati, Adillah; Fakhrudin, Nanang (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
Brown macroalgae (BM) which contain fucoxanthin exhibited high antioxidant activity. This study was performed to examine antioxidant, anti-collagenase, anti-elastase, anti-tyrosinase activities, and effect on cell viability of Human Dermal Fibroblast adult (HDFa) of BM, Turbinaria decurrens Bory. T. decurrens dried powder were macerated by ethanol to obtain extract (ETD) and was fractination by column chromatography to obtain fraction (FTD). Fucoxanthin content was determined using HPLC. The antioxidant activities, anti-collagenase, anti-elastase, and tyrosinase inhibitory assay were performed. The effect of ETD and fucoxanthin standard on cell viability were conducted on HDFa cell-induced by hydrogen peroxide (H2O2). The HPLC analysis showed that ETD and FTD contain fucoxanthin of 284.9±3.3µg/g and of 653.4±30.6µg/g dry-weight, respectively. The antioxidant assay showed that ETD and FTD produced high antioxidant activity by ferric reducing antioxidant power (FRAP) and b-carotene bleaching (BCB) methods that were comparable to fucoxanthin. ETD exhibited significantly higher tyrosinase inhibitory than kojic acid (p<0.01), while FTD had a comparable effect to kojic acid. The result also revealed that ETD and FTD produced anti-elastase and anti-collagenase (matrix metalloproteinase-1 (MMP-1). Fucoxanthin and ETD were able to maintain cell viability on HDFa cell-induced H2O2. This study suggests that T. decurrens may be effective to prevent skin aging and wrinkle formation, possibly through the antioxidant activity and maintain cell viability of fibroblast.